The Challenge of Distinguishing Between Cholangiocarcinoma and IgG4-related Sclerosing Cholangitis - Chang, Emer; Culver, Emma (Journal of the Nuffield Department of Surgical Sciences, 2023)
This case report summarises Mr X’s clinical history examination and focuses on the diagnosis of his cholangiocarcinoma. Here, we discuss the extent to which we can distinguish cholangiocarcinoma from a similarly presenting but distinct condition: IgG4-related sclerosing cholangitis. Highlighting advances in diagnosis of each disease and providing suggestions for how this may be applied to better distinguish between the two diseases, whilst also considering the patient’s lived experience of uncertainty surrounding their diagnosis.